Eurozone sovereign bonds and rating assessments: impact on volatility - Wrana, Javier; Martín, José María (Papeles de Europa, 2014)
Rating agencies have been very active during the economic crisis and have been blamed for damaging the refinancing possibilities of the eurozone countries. Their decisions concerning sovereign bonds have been widely pointed out as one of the reasons why spreads rose dramatically between 2009 and 2012. Nonetheless, last evolutions of the sovereign spreads in countries such as Spain, Ireland or France show that sovereigns do not respond to rating assessments as extremely as they did before. Therefore, economic actors may wonder whether there has been a recent change in the trend or by contrast those assessments did not influence the volatility of the spreads, which may have been motivated by other variables. In this paper we will intend to determine to what extent S&P announcements were drivers of higher volatility of sovereign bonds’ spreads and how these effects (if any) have evolved over the economic crisis.
Keywords: Rating agencies; sovereign bonds; volatility; economic crisis